Status Gizi, Asupan Makan, dan Durasi Tidur Anak Sekolah: Studi Komparasi: Nutritional Status, Dietary Intake, and Sleep Duration Among School Children: A Comparative Study - Wizara Salisa; Rachmahnia Pratiwi; Kamila Dwi Febrianti; Annis Catur Adi; Siti Rahayu Nadhiroh (Amerta Nutrition, 2023)
Background: There are differences in the prevalence of malnutrition between rural and urban areas due to differences in consumption patterns. However, data regarding differences between rural and urban areas in Indonesian cities still need to be investigated, even though this information is essential for the government to use when creating policies to eradicate malnutrition.    Objectives: To determine the effects of differences in school location (rural and urban) on the nutritional status, food intake, and sleep duration of children in junior high school. Methods: The research employed a cross-sectional design, which comprised 102 junior high school students in Jombang (a rural area) and 101 junior high school students from Surabaya (an urban area) served as the sample. Nutritional status was determined using anthropometric measurements of z-score BMI-for-age, performing the 2x24H food recall interviews to determine food intake and the questionnaire to determine sleep duration.     Results: The findings revealed a significant difference between rural and urban areas in nutritional status (p=0.002) and food intake, namely carbohydrate intake (p<0.001). The issue of malnutrition that differed significantly between the two regions was obesity (p<0.001), which was more prevalent in urban areas; on the other hand, undernutrition did not (p=0.556). In addition, sleep duration did not differ significantly (p=0.327).   Conclusions: In conclusion, differences in nutritional problems between urban and rural areas were not constantly caused by food intake or sleep duration; however, indirect factors such as physical activity could also play a role. This finding resulted in recommendations for schools to conduct a balanced nutrition education program and for the government to implement various policies to eliminate malnutrition in urban and rural areas.